Multiple ectopic recurrent germ cell tumors after total pineal mature teratoma removal: A case report and literature review - Han, Lei; Song, Ye; Fang, Luxiong; Qi, Songtao (Frontiers in Oncology, 2023)
Abstract Intracranial germ cell tumors (GCTs) are highly heterogeneous and rare, and the recurrence of mature teratomas is uncommon. There is limited data on the systematic management of multiple recurrent tumors following total teratoma removal. Herein, we report repeated relapsing GCTs with different histological subtypes and locations after en bloc total resection of a pineal mature teratoma. A 14-year-old patient underwent total resection of a tumor in the pineal region and histopathology revealed a mature cystic teratoma. Four years later, the patient experienced a recurrence of the suprasellar tumor, which occurred several times over the next eight years. The tumor was successfully eliminated after multiple surgeries, radiotherapy and chemotherapy. By the time the paper was submitted, the patient had not had a recurrence of the tumor and was in the good physical condition and leading a normal life. Based on this case, we discussed the pathogenesis of recurrent mature teratoma and the therapeutic strategy of multiple recurrent GCTs.